eIF3f como posible marcador pronóstico de leucemia linfoblástica aguda de células B (LLA-B) - Vergara Hernández, Jéssica Aneth (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
Acute lymphoblastic leukemia (ALL) is a public health problem that represents 50% of malignancies cases diagnosed in children under 18 years, the most common being B-ALL. Current treatments target cells in the S and M phases of the cell cycle. eIF3f has been described as a possible prognostic marker in other malignancies and correlates with some prognostic markers. We propose to evaluate the utility of eIF3f as a prognostic marker and its possible correlation with other markers for B-ALL. Overall objective: To determine if the expression of eIF3f represents the proliferative activity and if it has value as a prognostic marker in B-ALL and / or in other blood diseases. Materials and methods: Descriptive, correlational, analytical, and longitudinal study. Bioinformatic phase dependent cell cycle detection panel development and its standardization in cell line A549 and lymphocytes from healthy volunteers. Standardization of the protocol for processing blood origin samples with a surface response analysis (ARS). The analysis of eIF3f expression was performed by flow cytometry in bone marrow samples from patients from the oncology area of the Children’s Hospital of Morelia “Eva Sámano de López Mateos” with de novo diagnosis of ALL, as well as in quiescent and proliferative lymphocytes, by the addition of a mitogen (PHA), from volunteers without erythrocyte abnormalities and under 18 years of age, in order to obtain paired samples. Results: Forty samples were analyzed, which were divided into 2 groups based on the fluorochrome used for the detection of eIF3f (AlexaFluor-647 or FITC) and in subgroups based on the diagnosis (ALL, AML, diagnosis other than leukemia and patients with probable leukemia); each group was analyzed with its corresponding control.

La leucemia linfoblástica aguda (LLA) es un problema de salud pública que representa el 50% de los casos de neoplasias diagnosticadas en menores de 18 años, siendo la más común la LLA-B. El tratamiento actual está dirigido a células en las fases S y M del ciclo celular. eIF3f ha sido descrito como posible marcador pronóstico en otras neoplasias y se correlaciona con otros marcadores pronósticos. Se propone evaluar la utilidad de eIF3f como marcador pronóstico y su posible correlación con otros marcadores para LLA-B. Objetivo general: Determinar si la expresión de eIF3f representa la actividad proliferativa y si tiene valor como marcador pronóstico en LLA-B y/o en otras patologías hemáticas. Materiales y métodos: Estudio descriptivo, correlacional, analítico y longitudinal. Desarrollo bioinformático de un panel de detección de ciclo celular fase dependiente y su estandarización en la línea A549 y linfocitos de voluntarios sanos. Estandarización del protocolo de procesamiento de muestras de origen hemático con un análisis de respuesta de superficie (ARS). Se realizó un análisis de la expresión de eIF3f por citometría de flujo en muestras de médula ósea de pacientes con diagnóstico de novo de LLA del área de oncología del Hospital Infantil de Morelia “Eva Sámano de López Mateos”, así como en linfocitos en quiescencia y proliferativos por la adición de un mitógeno (PHA) en voluntarios sin alteraciones eritrocitarias y menores de 18 años, con la finalidad de obtener muestras pareadas. Resultados: Se analizaron 40 muestras que se dividieron en 2 grupos en base al fluorocromo utilizado para la detección de eIF3f (AlexaFluor-647 o FITC) y en subgrupos en base al diagnóstico (LLA, LMA, diagnóstico diferente a leucemia y pacientes con probable leucemia); cada grupo fue analizado con sus controles correspondientes.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-R-M-2020-0576; Ciclo celular; Citometría de flujo; Proliferación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3020